Core muscle injury: Evaluation and treatment in the athlete - Forlizzi, J. M.; Ward, M. B.; Whalen, J.; Wuerz, T. H.; Gill IV, T. J. (The American Journal of Sports Medicine, 2022)
Background: Pain in the groin region, where the abdominal musculature attaches to the pubis, is referred to as a "sports hernia,""athletic pubalgia," or "core muscle injury" and has become a topic of increased interest due to its challenging diagnosis. Identifying the cause of chronic groin pain is complicated because significant symptom overlap exists between disorders of the proximal thigh musculature, intra-articular hip pathology, and disorders of the abdominal musculature.